Lessons from an Evaluation of Five State Supported Delinquency Prevention Projects - Elrod, Preston (2004)
Presents an overview of findings from an evaluation of five state supported delinquency prevention projects that was conducted between July 1, 2001 and June 30, 2002. Each of the projects evaluated was funded as part of the Kentucky Community Partnerships to Prevent Delinquency Initiative. This initiative represented a major effort by the Commonwealth through its state Department of Juvenile Justice to assist communities in their efforts to develop local delinquency prevention plans and to fund programs that address local needs in eight geographic areas within the state that were identified by DJJ as having high levels of juvenile crime